Legal and bioethical foundations of human cell and tissue cryobanks in Ukraine: regulatory framework, challenges and prospects - Shapovalov, Valentyn; Nevzghoda, Oleksandr; Shapovalova, Viktoriia; Osyntseva, Alina; Shapovalov, Valerii (Problems of Cryobiology and Cryomedicine, 2026)
The paper considers the legal and bioethical foundations of the activity of cryobanks of human cells and tissues in Ukraine. The importance of adapting national legislation to international standards in the field of biobanking, transplantology and assisted reproductive technologies is shown. The study provides an analysis of the basics of legal regulation of cryobanks, identifies directions for improving the legislation of Ukraine in accordance with European standards. For the analysis, the authors were guided by the laws of Ukraine, directives of the European Union, recommendations of the World Health Organization, documents of the Council of Europe, and used scientific publications in the field of medical law, bioethics, cryobiology, and reproductive medicine. Regulatory, documentary, comparative methods of analysis were applied. It has been established that the current regulatory framework for governing the activities of cryobanks is fragmented, does not determine the legal status of biological material, the procedure for its inheritance and use after the donor’s death. The proposed ways to improve the legal field are as follows: adoption of a special law on biobanks, creation of a unified state register of biological samples, adaptation of protocols and procedures to the norms of the European Union. The implementation of the proposed measures will contribute to the transparency, ethics, and efficiency of cryobanks, the protection of the rights of donors and patients, and the development of biomedical research in Ukraine. Probl Cryobiol Cryomed. 2025; 35(4): 165—178